Polysomnography in idiopathic muscle pain syndrome (fibrositis) - A. B. Silva; T. E. Bertoríni; H. Lemmi (Arquivos de Neuro-Psiquiatria)
Muscle pain occurs in various neuromuscular disorders with characteristic physiological or biochemical abnormalities. There is, however, a group of patients in whom there is no clear physiological or structural basis for their pains. This syndrome has been called fibrositis or fibromyalgia. Sleep abnormalities have been reported in some of these patients, but have not been confirmed by others. We studied 8 patients with this disorder and found sleep abnormalities that were characterized by nocturnal myoclonus, alpha-delta sleep, and abnormalities compatible with depression. Polysomnography was, therefore, instrumental in helping direct the treatment of these patients. Therapeutic approaches aimed to correct the specific disorders were effective in improving the pain symptoms